Kompetanse for inkluderende praksis Et innovasjonsprosjekt om samarbeid mellom barnehage/skole og PP-tjenesten - Mjøs, Marit (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2023)
This anthology constitutes the primary report resulting from a three-year innovation project in which the main focus has been on collaboration between preschools and primary schools, and the 'PP-tjeneste' (pedagogisk-psykologisk tjeneste, a public service that assists in evaluation of children with special educational and/or psychological needs and helps those working in the educational setting make appropriate accommodations for those needs), and establishing a program in which they jointly develop their competence regarding inclusivity. Researchers from NLA University College, the University of Stavanger and Statped (a national service for special needs education) have formed a partnership to support a range of innovation processes as well as track their progress through data collection and analysis, and thereby respond to the profile set forth in the national strategy, 'Kompetanseløftet for spesialpedagogikk og inkluderende praksis' (Enhancements in special pedagogic and inclusive practices), initiated during the project period. The experiences presented in this anthology will therefore be relevant and of interest to many in both the higher educational sector and the municipalities.